Pengaruh Mobilisasi Progresif Level I TerhadapTekanan Darah Dan Saturasi Oksigen Pasien Stroke Non Hemoragik Dengan Penurunan Kesadaran Diruangan Intensive Care Unit (ICU) Rumah Sakit Immanuel Bandung - Dela Natalia Olin Hully (Jurnal Ilmu Kesehatan Immanuel, 2025)
Background: Stroke or CVA (Cerebro Vascular Accident), is the most common central nervous system disorder and is the main cause of functional activity disorders in adults. Stroke attacks will disrupt or reduce oxygen supply and generally cause serious damage or necrosis to brain tissue. The faster the brain's blood circulation returns to normal after a stroke, the better the patient's chances of a full recovery. Objective: to determine the effect of level 1 progressive mobilization on blood pressure and oxygen saturation in stroke patients with decreased consciousness. Method: The research design in this scientific paper uses a descriptive method in the form of a case study. This study aims to determine the problem of nursing care in non-hemorrhagic stroke patients with decreased consciousness. Results: There is an effect of level I progressive mobilization on blood pressure and oxygen saturation in stroke patients with decreased consciousness in three patients. Conclusion: Routine provision of level I progressive mobilization therapy can normalize blood pressure and stabilize oxygen saturation in stroke patients with decreased consciousness. Suggestion: This intervention can be recommended as part of standard nursing care practices in intensive care units.  Keywords: Stroke, Progressive Mobilization Level I, Blood pressure, Oxygen saturation